Semiotic Structure of Traditional Japanese Rural Space: Hagikura Village, Suwa Basin - Imazato, Satoshi (Public Journal of Semiotics, 2007)
This paper analyzes the semiotic structure of rural space in a traditional Japanese village, with an economic base of agriculture and forestry, mainly before the end of the country’s era of rapid economic growth. This examination defines the interrelationships among the domains of spatial classifications within the village: social space, land-use zones, folk taxonomy, places, village boundaries, symbolic space, and orientation. An abstract system of relationships can be regarded as the spatial deep structure (langue), in contrast to the surface-level structure of rural landscape (parole).